1999
DOI: 10.31899/pgy6.1022
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from community-based distribution of family planning in Africa

Abstract: This paper reviews findings and experiences from efforts to implement community-based family planning services in sub-Saharan Africa. Although research suggests that community-based service delivery can contribute to contraceptive use, the magnitude of impact is often in doubt or is considerably less than was observed in similar projects in Asia in the 1970s and 1980s. Reasons for the constrained impact of community-based family planning in Africa are reviewed and assumptions about the efficacy and mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 91 publications
0
37
0
Order By: Relevance
“…Field experiments to evaluate the impact of FPPs are, however, complex and expensive, which may account for their limited number to date (Bauman 1997;Bauman et al 1994;Phillips et al 1999). The evaluation of an outreach family planning and health services project in the rural district of Matlab, Bangladesh, is perhaps the most widely cited social experiment.…”
Section: The Impact Of Family Planning Programs and Microcredit On Fementioning
confidence: 99%
“…Field experiments to evaluate the impact of FPPs are, however, complex and expensive, which may account for their limited number to date (Bauman 1997;Bauman et al 1994;Phillips et al 1999). The evaluation of an outreach family planning and health services project in the rural district of Matlab, Bangladesh, is perhaps the most widely cited social experiment.…”
Section: The Impact Of Family Planning Programs and Microcredit On Fementioning
confidence: 99%
“…CBD programs provide health commodities outside the traditional clinical setting, usually through trained community members who operate at the village level (Katz et al 1998;Ande, Oladepo, and Brieger 2004;Gazi et al 2005). Programs date as far back as the 1960s, when the first family planning CBD programs originated in Asia and quickly extended across the continent and into Africa and Latin America (Phillips, Greene, and Jackson 1999). By the mid-1990s, the German Technical Cooperation (GIZ), the United Nations Population Fund (UNFPA), and USAID funded contraceptive CBD programs (Phillips, Greene, and Jackson 1999).…”
Section: March 2015mentioning
confidence: 99%
“…Another review of African CBD services concluded that further research is needed to identify successful CBD strategies and examine reasons for their failure and success (Phillips and Green, 1993). One strategy to improve program planning and implementation of community-based familyplanning services is a quality assurance approach which focuses on the quality of care and clients' perceptions of and satisfaction with the program.…”
Section: Introductionmentioning
confidence: 97%
“…Phillips et al (1999) reported that it is generally more critical to overcome the social than the geographic barriers to contraceptive services.…”
Section: Introductionmentioning
confidence: 98%